Universities and Epistemology: From a Dissolution of Knowledge to the Emergence of a New Thinking - Ronald Barnett; Søren Bengtsen (MDPI AG, 2017)
This paper examines the relation between epistemology and higher education. We shall start by briefly examining three classical texts on the understanding of knowledge at universities, as well as noting some others, and go on to sketch a version of our own. Our argument is as follows: the world is such that the relationship between the university and knowledge remains fundamental but that it needs to be reconceptualised. In particular, the 21st century is seeing the emergence of digital reason, which could be said to be a form of non-reason. It may appear, therefore, that we are witnessing the dissolution or severing of the relationship between the university, on the one hand, and knowledge and truth on the other hand. To the contrary, we argue for what we term an ecological perspective on knowledge, with the concept of ecology being treated in the most generous way, partly as a way of rethinking the university into the future. The idea of knowledge as a defining concept of the university still has mileage in it.